Alcalóides de Erythrina Velutina Willd: caracterização por cromatografia gasosa e líquida acoolada a espectrometria de massas - Leal, Natasha Lorenna Ferreira da Silva (2018)
The genus Erythrina presents about 110 species, of which 70 are native to the Americas with dissemination mainly in the tropical and subtropical regions. This genus belongs to the Fabaceae family. The species studied Erythrina velutina popularly known as swine, mulungu, pocket knife, corticeira, eritrinamulungu and parrot beak. It is distributed in Brazil from the Northeast to Minas Gerais. In folk medicine it is used as a tranquilizer and for other disorders in the central nervous system such as insomnia and depression. Species of the genus are very important in the pharmaceutical industry for the production of anxiolytic herbal medicines. The chemical markers of the genus Erythrina are the erythrin alkaloids, which are attributed to anxiolytic activity. In view of this, this work aims to contribute to the expansion of chemical knowledge of the genus, through the characterization of alkaloids from the stem bark of E. velutina Willd. by gas chromatography coupled to mass spectrometry and high performance liquid chromatography coupled to mass spectrometry. For the study, the dry and crushed plant material was subjected to extraction by exhaustive maceration and concentrated in a rotary evaporator, posteriorly by means of acid-base extraction the fraction of total alkaloids was obtained and then the same was analyzed by mass spectrometry with electron ionization and electrospray ionization mass spectrometry. With the results it was possible to observe the presence of erythrin alkaloids in the fraction of total alkaloids of the ethanolic extract of the stem bark of the species in study, being them: erysodyne or erysovine, erythrascine, erythraline, erytraditine or its epimer, erymelanthine, erysotina or erysosalvine, Hidroxerisosalvina/ hidroxierisotina, erythratine, erysothrine, erythrinine, eritroculin and erythratine N- oxide. With the exception of erytraline, erysothrine, erysodine, erysovine e erythratine the other substances are first reported for E. velutina.